Experimental investigations on air/particle flow characteristics in a 2000 t/d GSP pulverized coal gasifier with an improved burner. (15th December 2018) - Fang, Neng; Li, Zhengqi; Wang, Jiaquan; Zhang, Bin; Zeng, Lingyan; Chen, Zhichao; Wang, Haopeng; Liu, Xiaoying; Zhang, Xiaoyan
Abstract: Removing end surfaces of a multi-channel burner which is the most commonly used burner type in entrained flow gasifiers could ease the risks of burner and cooling screens burning. On an air-particle test facility, experiments were conducted to investigate the influence of the improvements in a 2000 t/d GSP gasifier on the air/particle flow characteristics using a particle dynamics anemometer. For GSP burner and improved GSP burner (IGSP burner), the M-shaped distribution of mean axial velocity appears at the cross-section x/d  = 4 and 6, respectively. By removing the end surface, the air and particles first diffusing to the near-wall region under the IGSP burner is delayed resulting in a lower risk that the cooling screen is burned. In IGSP burner, the central recirculation zone is smaller in both radial and axial directions than in GSP burner; removing the end surface could reduce the risk of burner being burned. Industrial-sized experimental results uncovered that in comparison with the prior GSP burner, the heat absorption of the burner support and the four parallel cooling screens for the IGSP burner decreased by 22% and 53%, respectively, which effectively verified the validity of the structural improvement. Highlights: End surfaces at the exit of a multi-channel burner were removed. Air/particle flow fields under the improved burner were measured in lab-scale. The influence of the improvements on the air-particle mixture extent was given. The improvements mitigated high temperature corrosion to cooling screen and burner.